Judicial review of illegal clauses in consumer loan agreements - Fibinger-Jasińska, Justyna (Scientific Journal of Bielsko-Biala School of Finance and Law, 2023)
The Consumer Credit Act of 12 May 2011 introduced, with effect from 11 March 2016, Article 36 a 1, which specifies the maximum amount of non-interest credit costs. The maximum amount of these costs is calculated according to a formula (Article 36a (1)), and additionally, these costs over the entire duration of the credit may not be higher than the total amount of credit (paragraph 2). On the other hand, with effect from 30 May 2010, Article 304 CC was amended to include new paragraphs 2 and 3-2, aimed at protecting the consumer from excessive benefits in loan agreements. According to the author of the article, the provisions aimed at protecting the consumer against unfair practices of lending entrepreneurs are insufficient and, despite the implementation of Directive 93/13/EEC, do not provide sufficient consumer protection. Therefore, the court deciding the case should always ex officio examine whether contractual provisions constitute prohibited clauses.